Evaluation of Biodentine in the Restoration of Root Caries: A Randomized Controlled Trial. (April 2016) - Hayes, M.; da Mata, C.; Tada, S.; Cole, M.; McKenna, G.; Burke, F.M.; Allen, P.F.
There is no "gold-standard" material for the operative management of root caries. The aim of this study was to determine if the clinical performance of Biodentine would be acceptable for the restoration of root caries in older adults. A randomized controlled clinical trial was conducted comparing a calcium silicate cement (Biodentine), a high-viscosity glass ionomer cement (Fuji IX GP Extra), and a resin-modified glass ionomer cement (Fuji II LC). Of the 334 volunteers assessed for eligibility, 249 were excluded. A total of 303 lesions in 85 participants were randomized, with 151 lesions allocated to receive Biodentine, 77 to Fuji IX GP Extra, and 77 to Fuji II LC. Patients were reviewed by a calibrated dentist who was not involved in restoration placement and who was blinded to material allocation. Restorations were assessed according to a modified US Public Health Service criteria. The cumulative survival percentages after 6 mo and 1 y were 58.6% and 47.2% in the Biodentine group, 89.6% and 83.8% in the Fuji IX GP Extra group, and 89.5% and 84.9% in the Fuji II LC group, respectively. There were statistically significant differences ( χ 2 test, P < 0.001) in restoration failure rates between restoration groups. There was no difference between Fuji IX GP Extra and Fuji II LC, but differences ( P < 0.001) were shown between the Fuji II GP Extra group and the Biodentine group and also between the Fuji II LC group and the Biodentine group at both time points. Based on the results of this study, Biodentine cannot be recommended for the operative management of root caries. Fuji IX GP Extra and Fuji II LC displayed similar success rates, and high-viscosity glass ionomer cement and resin-modified glass ionomer cement continue to be the best available option for the restoration of root caries (ClinicalTrials.gov NCT01866059). Knowledge Transfer Statement: The results of this study can assist dental practitioners when selecting a restorative material for the operative management of root caries. This randomized controlled trial compared the 1-y clinical performance of a calcium silicate–based material to that of a high-viscosity glass ionomer cement and a resin-modified glass ionomer cement in the operative management of root caries. The study concluded that high-viscosity glass ionomer cement and resin-modified glass ionomer cement continue to be the best available option to dental practitioners when restoring the root surface.